My Room, My Home, My Self: Objects of memory in residential aged care. (4th May 2018) - Connellan, Kathleen
Abstract: The material culture of home cannot be supplanted in its entirety when moving into an aged care facility. When the time comes, the decision of what to take and what to leave behind is not simple. This article presents the balance between practical and emotional considerations in the choice and presence of personal objects in the rooms of residents. Intersubjective relationships between material objects in the room and the people who enter that space is viewed through a narrative lens. In this way, it is the materiality of the room-as-home for the self, which is key. Three major themes relating to the objects in the room of the older person were found to be: 1. Safety, 2. Family, and 3. Home. These themes emerged from ethnographic research in an aged care setting. Participants included residents, their families, care staff, and management of the facility. The article contributes to understandings of material objects as carriers of identity and meaning in an aged care facility.